Decision Support System For The Best Employee Selection Recommendation Using Ahp (Analytic Hierarchy Process) Method - Rudi Hermawan; Muhammad Tri Habibie; Danang Sutrisno; Arman Syah Putra; Nurul Aisyah (CV. Inara, 2021)
The background of this research is how to create a system that can help humans in deciding something, without taking sides with one party, and deciding something to the maximum, with this system it can be done using a decision-making system and using the AHP method which is applied to selection of the best employees in a company. The method used in this research is to use the literature review method, and read a lot of books, so that journals can be the basis of this research, with this basis, they can find the latest research problems and can be raised in this study, so finding novelty in this research, so that it can be used for future research. The problem raised in this research is how to create a system that can help decide without having to side with anyone and can help company leaders in deciding who is the best employee in their company. This research produces an output that can be known who is the best employee in a company, the best employee in a company to Bambang Wijaya with a point value of 440, which is given directly by the company's leaders so that this value is an absolute value and cannot be changed by anyone.